Targeting of blood safety measures to affected areas with ongoing local transmission of malaria. Issue 3 (30th May 2016) - Domanović, D.; Kitchen, A.; Politis, C.; Panagiotopoulos, T.; Bluemel, J.; Van Bortel, W.; Overbosch, D.; Lieshout‐Krikke, R.; Fabra, C.; Facco, G.; Zeller, H.
SUMMARY: An outbreak of locally acquired Plasmodium vivax malaria in Greece started in 2009 and peaked in 2011. Targeting of blood safety measures to affected areas with ongoing transmission of malaria raised questions of how to define spatial boundaries of such an area and when to trigger any specific blood safety measures, including whether and which blood donation screening strategy to apply. To provide scientific advice the European Centre for Disease Prevention and Control (ECDC) organised expert meetings in 2013. The outcomes of these consultations are expert opinions covering spatial targeting of blood safety measures to affected areas with ongoing local transmission of malaria and blood donation screening strategy for evidence of malaria infection in these areas. Opinions could help EU national blood safety authorities in developing a preventive strategy during malaria outbreaks.